(untitled) (Geographica Pannonica, 2020)
In the article authored by Milošević D., Dunjić J., and Stojanović V., entitled „Investigating micrometeorological differences between steppe, forest-steppe and forest environment in northern Serbia during a clear and sunny autumn day“ which was published in issue 3 (vol. 24) of Geographica Pannonica journal, one of the stated formulas (Method and data section, page 180, Humidex formula) has been misspelled in the stage of technical preparation of the article. We sincerely apologize to the readers for the inconvenience. With the author’s permission, in this issue, we publish the corrected formula.